1990
DOI: 10.1002/tea.3660271011
|View full text |Cite
|
Sign up to set email alerts
|

Students' misunderstandings and misconceptions in college freshman chemistry (general and organic)

Abstract: Both chemistry teachers and nonmajor students appear to agree that freshman chemistry may well be the most problematic traditional science discipline taught in the first year of college-as far as students' misunderstandings, learning dificulties, and misconceptions are concerned. The above is probably due to the many abstract, nonintujtive concepts, which are not directly interrelated. Consequently, in such cases, the powerful, general teaching strategy of "concept mapping" must be replaced by alternative, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0
27

Year Published

1992
1992
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(144 citation statements)
references
References 17 publications
1
116
0
27
Order By: Relevance
“…Thus, it can be concluded that concept mapping involved students who mastered concept mapping in actively relating new information to prior knowledge resulting in meaningful learning and consequently higher achievement. This situation, however, does not suggest that concept mapping is a solution for all problems in learning chemistry because, as Zoller (1990) suggests, there are chemistry concepts that are abstract, nonintuitive, and not directly interrelated and cannot be taught by using concept mapping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it can be concluded that concept mapping involved students who mastered concept mapping in actively relating new information to prior knowledge resulting in meaningful learning and consequently higher achievement. This situation, however, does not suggest that concept mapping is a solution for all problems in learning chemistry because, as Zoller (1990) suggests, there are chemistry concepts that are abstract, nonintuitive, and not directly interrelated and cannot be taught by using concept mapping.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are disagreements between researchers on the effectiveness of concept mapping in chemistry teaching. Zoller (1990), for example, questions the effectiveness of concept mapping in chemistry because many chemistry concepts are abstract, nonintuitive, and not directly interrelated. In contrast, Novak (1994) argues that the problems are not due to the nature of chemistry; problems rather arise from the fact that students learn chemistry by rote and do not recognize key concepts and their relationships.…”
Section: Concept Mappingmentioning
confidence: 99%
“…Chemsitry curriculum generally combines numerous abstract concepts in which they are the center of learning Chemistry and any other disciplines [1]. These concepts are essential because advanced chemistry or science concept or science theory are not easy to be understood if the underlying concepts are not really understandable for the students ( [2], [3], [4], [5]). The abstracts characteristics in Chemistry along with the difficulties in other learning content (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Choose language (spoken and written) carefully and pay particular attention to students' speaking and writing, offering gently constructive suggestions for better words and turns of phrase. Engage in Socratic dialectic to "unteach" misconceptions, replacing them with proper alternatives (Zollar 2011). …”
Section: Tackling Preconceptions Head-onmentioning
confidence: 99%